2018
DOI: 10.2147/dddt.s137106
|View full text |Cite
|
Sign up to set email alerts
|

Clinical potential of mechlorethamine gel for the topical treatment of mycosis fungoides-type cutaneous T-cell lymphoma: a review on current efficacy and safety data

Abstract: Nitrogen mustard is a chemotherapeutic agent that has a well-documented safety and efficacy profile in the treatment of cutaneous T-cell lymphoma. Development of nitrogen mustard formulations and treatment regimens has been studied extensively over the last 40 years. In the last 5 years, a new gel formulation has been developed that is associated with a decrease in delayed hypersensitivity reactions. The authors in this review found that while the gel formulation may result in a decrease of allergic contact de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
1
16
0
2
Order By: Relevance
“…Adverse effects of mechlorethamine include immediate hypersensitivity reactions (allergy), erythema, hyperpigmentation, and pruritis. Secondary malignancies like cutaneous melanoma, nonmelanoma skin cancer, and primary malignancies were also reported [ 39 , 40 ]. Glucocorticoids may trigger tachyphylaxis [ 41 ] and, as CTCL patients are treated for a long time, their therapeutic potential is therefore limited.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse effects of mechlorethamine include immediate hypersensitivity reactions (allergy), erythema, hyperpigmentation, and pruritis. Secondary malignancies like cutaneous melanoma, nonmelanoma skin cancer, and primary malignancies were also reported [ 39 , 40 ]. Glucocorticoids may trigger tachyphylaxis [ 41 ] and, as CTCL patients are treated for a long time, their therapeutic potential is therefore limited.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported efficacy data on treatment with mechlorethamine aqueous solutions. A recent review highlighted the difficulty in comparing them, as the frequency and duration of treatment varied, together with the use of additional therapies 46. However, the complete response (CR) rate reported was 51%–84% in T1 patients and 34%–62.2% in T2 patients 46.…”
Section: Management Of Mycosis Fungoidesmentioning
confidence: 99%
“…Following this study, the treatment was approved by the FDA in 2013, in Israel in 2016, and in France in September 2017, after temporary individual and then cohort authorization of use since 2014. It offers the advantage of better adherence, as the greasiness of the ointment was often highlighted 46…”
Section: Management Of Mycosis Fungoidesmentioning
confidence: 99%
See 2 more Smart Citations